2019
DOI: 10.1038/s41598-018-37252-9
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal fluid from Alzheimer’s disease patients as an optimal formulation for therapeutic application of mesenchymal stem cells in Alzheimer’s disease

Abstract: Mesenchymal stem cells (MSCs) have emerged as one of the promising treatment options for Alzheimer’s disease (AD). Although many studies have investigated on the efficacy of MSCs in AD, how MSCs actually change following exposure to the AD environment has not been studied extensively. In this study, we investigated on the potential of AD patient-cerebrospinal fluid (CSF) samples to be used as a formulation of MSCs and its application in AD therapeutics. When Wharton’s jelly-derived mesenchymal stem cells (WJ-M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…The differentiation of the WJ-MSCs was tested according to the procedure outlined in a previous report [ 49 ].…”
Section: Methodsmentioning
confidence: 99%
“…The differentiation of the WJ-MSCs was tested according to the procedure outlined in a previous report [ 49 ].…”
Section: Methodsmentioning
confidence: 99%
“…Human Warton’s jelly-derived MSCs from a single donor at passage 5–6 were used in this study. Stemness of MSCs was confirmed using in vitro differentiation assays into osteogenesis, adipogenesis, and chondrogenesis and flow-cytometric analysis for cell surface markers (CD73, CD90, CD105, CD166, CD14, CD11b, HLA-DR (MHCII), CD34, CD45, and CD19), as described previously [39]. After getting 90% confluence, MSCs were preconditioned with thrombin (2 U/mL; Sigma–Aldrich, Steinheim, Germany) in culture medium (α-MEM; Gibco, Life Technologies, Carlsbad, CA, USA) for 3 h. Control naïve MSCs were prepared in the same manner except for the thrombin treatment.…”
Section: Methodsmentioning
confidence: 99%
“…First, since the cerebrospinal fluid (CSF) flows along the surface of the spinal cord up towards the brain, MSCs can be delivered into the entire neuraxis. One of our previous studies showed that the CSF from normal elderly or Alzheimer patients does not affect the stemness of MSCs [22]. Thus, we expect that the therapeutic potential of the MSCs will not be affected when injected via the intrathecal route.…”
Section: Introductionmentioning
confidence: 91%